A device for generating binary digit pseudo-random sequences (1984)
A device which comprises a binary digit pseudo random sequence source (4) and four Exclusive-OR logic circuits (20, 21, 22, 23) for coupling said source to logic apparatus, to which four lines are coupled for transmitting logic data (T1, T2, T3, T4)having a predetermined frequency and supplying at the output (a) of a multiplexer (1) a multiplexer signal having a frequency which is four times the predetermined frequency and responsive to the control of the subject device, in such a way as to define for said multiplexed signal a pseudo-random sequence having a period 2 -1 for tributary data T1=T2=T3=T4=logic level "0". DISPOSITIVO PARA GENERAR SECUENCIAS PSEUDO-ALEATORIAS DE DIGITOS BINARIOS, EL CUAL ESTA ASOCIADO CON UN APARATO LOGICO AL QUE SE ACOPLAN CUATRO LINEAS PARA TRANSMITIR LOS DATOS LOGICOS QUE TIENEN UNA FRECUENCIA QUE ES CUATRO VECES LA MENCIONADA FRECUENCIA Y QUE RESPONDE AL CONTROL DE DICHO DISPOSITIVO. CONSTA DE SIETE BLOQUES SECUENCIALES SEMEJANTES (A1, A2, A3, A4, A5, A6, A7), EN CADA UNO DE LOS CUALES ESTA INDICADO RESPECTIVAMENTE LA ENTRADA (D), LA SALIDA (Q), LA ENTRADA DE RELOJ (CK) Y LA ENTRADA DE PRESELECCION (PR); DE CUATRO CIRCUITOS LOGICOS "AND" DE DOS ENTRADAS; DE CUATRO CIRCUITOS LOGICOS "EXCLUSIVOS-OR", CUYAS PRIMERAS ENTRADAS SE ACOPLAN CORRESPONDIENTEMENTE A LAS SALIDAS DE LOS CIRCUITOS LOGICOS "AND"; Y DE UN MULTIPLEXOR EQUIPADO CON CUATRO ENTRADAS A LAS QUE SE ACOPLAN LAS SALIDAS DE LOS CIRCUITOS "EXCLUSIVOS-OR".